2003
DOI: 10.1097/00042752-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Risk Factors, and Clinical Manifestations of Hyponatremia in Marathon Runners

Abstract: 21 runners presented to the medical area of the Houston Marathon with hyponatremia (.31% of entrants). Excessive fluid consumption and longer finishing times were the primary risk factors for developing this condition. Vomiting was the only clinical sign differentiating hyponatremia from other conditions that induce exercise-associated collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
5
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(175 citation statements)
references
References 23 publications
5
161
5
4
Order By: Relevance
“…However, recent studies have shown that endurance athletes not uncommonly develop hyponatremia at the end of the race, usually in the absence of clear central nervous system symptoms (9,10,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). For example, in the 2002 Boston Marathon, Almond et al (15) found that 13% of 488 runners studied had hyponatremia (defined as a serum sodium concentration of 135 mmol/L or less) and 0.6% had critical hyponatremia (serum sodium concentration of 120 mmol/L or less).…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have shown that endurance athletes not uncommonly develop hyponatremia at the end of the race, usually in the absence of clear central nervous system symptoms (9,10,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). For example, in the 2002 Boston Marathon, Almond et al (15) found that 13% of 488 runners studied had hyponatremia (defined as a serum sodium concentration of 135 mmol/L or less) and 0.6% had critical hyponatremia (serum sodium concentration of 120 mmol/L or less).…”
Section: Incidencementioning
confidence: 99%
“…During this period, military recruits were encouraged to ingest 1.8 L of fluid for every hour they were exposed to temperatures above 30°C (30). At least four other deaths have been attributed to EAH in the United States (5,10,11,26,31). It is interesting that two of these deaths occurred in doctors (31).…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatic hyponatremia (typically associated with serum sodium concentrations of less than 125-130 mEq/ AG-PPKN-0909 R1 CH33 04-07-06 12:03:36 L) has been observed during marathon and ultramarathon competition, [74][75][76] military training, 77,78 and recreational activities. 79 In athletic events, the condition is more likely to occur in females and slower competitors.…”
Section: Hyponatremiamentioning
confidence: 99%
“…1991). La disminución de electrolitos, puede inducir hiponatremia o hipokalemia (Allan, Wilson, 1971), y afectar el rendimiento del deportista, como también generar efectos negativos a su salud (Casa, Clarkson & Roberts, 2005;Hew, Chorley, Cianca & Divine, 2003;Castro-Sepulveda et al 2014). Por lo señalado anteriormente, es de gran importancia escoger una bebida rehidratante apropiada, donde una correcta combinación de macronutrientes y una adecuada selección y cantidad de electrolitos es fundamental (Casa, Clarkson & Roberts, 2005;Mayol & Aragon, 2009).…”
Section: Introductionunclassified